Collaborative Governance dalam Perlindungan Kepada Korban Kekerasan Seksual di Kota Padang - Noor, Amatul; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2024)
The high rate of sexual violence in Padang City has encouraged the government to collaborate with non-governmental organizations and the community to protect victims. This research describes the application of collaborative governance in efforts to protect victims of sexual violence in Padang City. This research collected data through interviews, documentation, literature review, and data presentation using a descriptive qualitative method. The results showed that collaborative governance in the collaboration network is running quite well. However, there are several obstacles, such as the lack of commitment of stakeholders in evaluation meetings, budget limitations, the unavailability of a representative Safe House, and the lack of quantity of human resources (HR). This study concludes that improving the quality of services and procurement of facilities and infrastructure needs to be done so that protection for victims of sexual violence in Padang City can be improved in the future.